2017
DOI: 10.1016/j.jpainsymman.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Level of Care Preferences Among Nursing Home Residents With Advanced Dementia

Abstract: Context Delivering goal-directed care is a hallmark of high-quality palliative care, but requires an understanding of preferences. Objectives To describe and identify factors associated with level of care preferences among proxies of nursing home (NH) residents with advanced dementia. Methods NH residents with advanced dementia and their proxies (N = 402 dyads) were recruited from 62 Boston-area facilities as part of an ongoing randomized clinical trial. At baseline, all proxies were asked to select which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 12 publications
4
41
0
Order By: Relevance
“…This suggests that the differences in hospitalization rates in this sample may be better explained, at least in part, by resident characteristics, such as age, functional status, and cognitive functioning, than by ACP status alone . This reflects prior research suggesting preferences for comfort‐focused care increase with advanced age and decreased cognition …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This suggests that the differences in hospitalization rates in this sample may be better explained, at least in part, by resident characteristics, such as age, functional status, and cognitive functioning, than by ACP status alone . This reflects prior research suggesting preferences for comfort‐focused care increase with advanced age and decreased cognition …”
Section: Discussionsupporting
confidence: 59%
“…6 In nursing facilities, residents and family members of incapacitated residents frequently elect to focus on comfort and avoid hospital transfers. [7][8][9] Hospital transfers are associated with negative consequences for nursing facility residents. 10 Several studies have found associations between comfort-focused goals of care and lower rates of hospitalization.…”
mentioning
confidence: 99%
“…It is possible that the high rates of hospitalization were concordant with individual care preferences. However, the majority of patients with dementia and their families and/or caregivers prefer a more conservative approach to their care, making this limitation less likely . Contrarily, the reason for the limited inpatient discretionary diagnostic workup or interventions for hospitalized patients may be related to goals of care discussions and resultant goal‐concordant care, which would subsequently affect the calculated diagnostic yield of inpatient evaluation.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition to longer‐term adverse outcomes, patients with dementia are at increased risk for an “intervention cascade” while hospitalized. With advancing stages of dementia, an increasing majority of patients’ and their family's care preferences prioritize comfort and more conservative management that aims to limit intensive diagnostic evaluations and invasive interventions …”
mentioning
confidence: 99%
“…1,2 Palliative care may benefit patients and families facing advanced-stage Alzheimer’s disease and other neurodegenerative dementias, most of whom prefer comfort-focused care. 3 These incurable and progressive diseases affect more than 5 million Americans and have extraordinary societal and family costs. 4,5 Dementia is associated with high rates of hospitalization, care transitions, and 30-day readmissions.…”
Section: Introductionmentioning
confidence: 99%